Application of the adverse outcome pathway framework for investigating skin sensitization potential of nanomaterials using new approach methods. (5th October 2020) - Bezerra, Soraia F.; dos Santos Rodrigues, Bruna; da Silva, Artur C. G.; de Ávila, Renato I.; Brito, Hallison R. G.; Cintra, Emílio R.; Veloso, Danillo F. M. C.; Lima, Eliana M.; Valadares, Marize C.
Abstract: Background: Currently, considerable efforts to standardize methods for accurate assessment of properties and safety aspects of nanomaterials are being made. However, immunomodulation effects upon skin exposure to nanomaterial have not been explored. Objectives: To investigate the immunotoxicity of single‐wall carbon nanotubes, titanium dioxide, and fullerene using the current mechanistic understanding of skin sensitization by applying the concept of adverse outcome pathway (AOP). Methods: Investigation of the ability of nanomaterials to interact with skin proteins using the micro‐direct peptide reactivity assay; the expression of CD86 cell surface marker using the U937 cell activation test (OECD No. 442E/2018); and the effects of nanomaterials on modulating inflammatory response through inflammatory cytokine release by U937 cells. Results: The nanomaterials easily internalized into keratinocytes cells, interacted with skin proteins, and triggered activation of U937 cells by increasing CD86 expression and modulating inflammatory cytokine production. Consequently, these nanomaterials were classified as skin sensitizers in vitro. Conclusions: Our study suggests the potential immunotoxicity of nanomaterials and highlights the importance of studying the immunotoxicity and skin sensitization potential of nanomaterials to anticipate possible human health risks using standardized mechanistic nonanimal methods with high predictive accuracy. Therefore, it contributes toward the applicability of existing OECD (Organisation for Economic Co‐operation and Development) testing guidelines for accurate assessment of nanomaterial skin sensitization potential. Abstract : (A ) Control cells with nonspecific background illumination. CytoViva hyperspectral imaging of (B ) single‐wall carbon nanotubes (SWCNs), (C ) titanium dioxide (TiO2 ), and (D ) fullerene (C60 ) internalized into human HaCaT keratinocytes after 2 hours of exposure. Scale bar: 3 μm.